Optimizing Transportation Costs Using the Minimum Cell Cost Method in the "Yusril Medan Bread Distribution" Business - Harahap, Lokot Muda; Febrianda, Dava; Ariani, Putri; Syahfitri, Rinanda Suci; Ritonga, Zulfikar Ali (Economic: Journal Economic and Business, 2024)
This research aims to solve problems regarding transportation costs in distributing Pak Yusril's Bread Business by using the minimum cell cost method, where this method is used to allocate bread to distribution areas with the minimum possible transportation costs. Pak Yusril's bakery business operates in several areas, namely: Medan Tembung, Medan Denai, Medan Area and East Medan. This research methodology includes primary and secondary data collection and analysis using a transportation model with a minimum cell cost method approach. The results of the method findings mean that the minimum cell cost that Mr. Yusril must pay is IDR. 163,500 with delivery of 150 baskets of bread every week. This research shows that the application of the minimum cell cost method is effective in optimizing transportation costs and increasing distribution efficiency.